United Nations Peacekeeping and the Principal of Non-Intervention: A TWAIL Perspective by Jennifer Giblin - Madeeha Umair Malik (NUST Journal of International Peace and Stability)
Jennifer Giblin’s United Nations Peacekeeping and the Principle of Non-Intervention: A TWAIL Perspective critically examines the evolution of UN peacekeeping through the lens of Third World Approaches to International Law (TWAIL). The book challenges whether contemporary peacekeeping missions truly adhere to the principle of non-intervention or serve as instruments of Western influence. Giblin explores the legal and normative foundations of peacekeeping, scrutinizing the erosion of consent, impartiality, and the non-use of force in operations, particularly in the Democratic Republic of Congo. While offering a compelling critique of entrenched power imbalances, the book’s reliance on a single case study raises questions about generalizability. Nonetheless, it provides a valuable contribution to understanding the complexities of UN peacekeeping, sovereignty, and international legal norms in the Global South.